Intellectual Philosophy in Pondok Studies - KHAIRUL NIZAM BIN ZAINAL BADRI (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
Pondok studies are the legacy of the education system in the archipelago which is centered on customary, cultural and religious molds in the Malay-Islamic context. The influx of modern education into Malaya as a result of Western colonialism has not only marginalized the role of pondok studies, but also provoked negative criticism of the pattern of education practiced by pondok studies which is said to be outdated and irrelevant to meet market demands. Motivated by this statement, this study seeks to trace the education system practiced in cottage studies, which has been instrumental in producing many scholarly figures both locally and internationally. To carry out the study, qualitative methods were used, and a document analysis approach was chosen to examine books, journals and periodical articles related to the study subject. The results of the study found that the education system in the pondok studies, has its own uniqueness and privilege in developing human potential through the idea of thinking. In the pondok curriculum, the appreciation of thinking must be directed to true knowledge rather than based on conjecture. In conclusion, the pondok education system is still relevant to these cutting -edge educational needs. In fact, on the one hand, the pondok education system is seen as more effective and more honest in developing human potential in terms of thought and behavior at a time when the current education system is too inclined to produce factory-based human products, to meet capitalist wants.